A randomized phase 2a efficacy and safety trial of the topical Janus kinase inhibitor tofacitinib in the treatment of chronic plaque psoriasis - Ports, W.C.; Khan, S.; Lan, S.; Lamba, M.; Bolduc, C.; Bissonnette, R.; Papp, K. (British journal of dermatology (1951), 2013)
Summary Background Tofacitinib (CP‐690,550) is a novel Janus kinase inhibitor in development as an oral formulation for the treatment of several inflammatory diseases including psoriasis. Objectives This phase 2a study aimed to assess the efficacy, systemic safety, local tolerability and systemic pharmacokinetics of topical tofacitinib in mild‐to‐moderate plaque psoriasis. Methods Two tofacitinib ointment formulations were evaluated in this multicentre, double‐blind, vehicle‐controlled trial (NCT01246583). Seventy‐one patients were randomized 2 : 1 : 2 : 1 to 2% tofacitinib ointment 1, vehicle 1, 2% tofacitinib ointment 2 and vehicle 2, each administered twice daily for 4 weeks to a single fixed 300 cm2 treatment area containing a target plaque with or without one or more nontarget plaques and normal skin. Results The primary endpoint of percentage change from baseline in the Target Plaque Severity Score at week 4 demonstrated statistically significant improvement for ointment 1 [least squares mean (LSM) –54·4%] vs. vehicle 1 (LSM –41·5%), but not ointment 2 (LSM –24·2%) vs. vehicle 2 (LSM –17·2%). Secondary endpoints (target plaque area and Itch Severity Item) improved similarly for tofacitinib ointment vs. corresponding vehicle. Adverse event (AE) occurrence was similar across treatment groups. All AEs were mild or moderate and none were serious or led to subject discontinuation. One application‐site AE (erythema) was reported. Tofacitinib mean systemic exposure was minimal and was greater for ointment 1 than for ointment 2. Conclusions Tofacitinib ointment 1 was well tolerated and efficacious compared with vehicle for the treatment of plaque psoriasis. Further study of topical tofacitinib for psoriasis treatment is warranted. What's already known about this topic? Janus kinase (JAK) signalling has been implicated in the pathogenesis of psoriasis. Tofacitinib (CP‐690,550) is a novel, small‐molecule JAK inhibitor in development for the treatment of several inflammatory diseases: it has demonstrated efficacy in a phase 2b study in moderate‐to‐severe plaque psoriasis when given orally. Topical therapy is the more commonly used therapeutic option for psoriasis, but there is a need for improved topical treatments. What does this study add? In this phase 2a study, tofacitinib in an ointment formulation demonstrated efficacy, systemic safety and local tolerability during 4 weeks of treatment in patients with mild‐to‐moderate chronic plaque psoriasis. Dermal penetration of tofacitinib, a small‐molecule, was demonstrated. Topical application of tofacitinib has the potential to provide an additional therapeutic option for patients with plaque psoriasis.